Pengembangan Aplikasi Rekomendasi Produk Terbaik Pada Marketplace Bukalapak Bagi Dropshipper dan Reseller Menggunakan AHP-TOPSIS - Freddy Ajax Pratama; Faizatul Amalia; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
For dropshipper and reseller as sellers, speed and accuracy in choosing products to sell are important. The speed of choosing a product affects the speed of selling a new product, while the accuracy of choosing a product increases the chance the product can be sold. In choosing a product, the seller considers several criteria such as price, number of sales, reviews, and seller's reputation. Generally sellers sell as many products as possible. A reseller or dropshipper needs to assess up to dozens of products to get the desired product. The activity can take up time with days to weeks and is repeated every time a seller wants to sell a new type of product. This causes problems, more and more products are judged to increase the time needed to get the best product. To answer these problems, a web-based application was developed that can help sellers find products, compare desired products and provide recommendations on the best products from various products. Application development is done by iterative method with two iterations. Product searching is done by web scraping technique while product recommendations are carried out by the AHP-TOPSIS method. Application development produces 29 functional needs in iteration 1, 12 needs in iteration 2, one needs functional compatibility, use case diagrams, and use case scenarios. Testing on applications produces 100% valid functional testing, valid nonfunctional testing, User Acceptance Testing (UAT) is accepted by respondents as stakeholders and research subjects, and valid for testing the accuracy of the AHP-TOPSIS method. Scraper applications are made accepted by respondents.